Content Validity and Cognitive Interview Process of Semistructured Interview to Evaluate Psychosocial Factors Associated with Mental Health among Undergraduate University Students - Fayaz Ahmad Paul; Indrajeet Banerjee; Arif Ali; Danishwar Rasool Dar; Aadil Bashir; Priyanka Saikia (Indian Journal of Psychiatric Nursing)
Background: Content validity and cognitive interviewing are crucial elements in the development of measurement tools, impacting the psychometric properties and functionality of the instrument. Content validity ensures that the instrument adequately covers the intended content, while cognitive interviewing focuses on understanding respondents’ cognitive processes to identify questionnaire errors. Objective: This study aims to undertake content validation and cognitive interviews for a semistructured interview designed to measure psychosocial factors related to mental health among undergraduate university students. Materials and Methods: A qualitative and quantitative approach was employed in Tezpur, Assam. Six mental health experts verified the semistructured interview scale and conducted cognitive interviews with twenty undergraduate students. The study unfolded in three phases: (1) the creation of a 71-item pool, (2) content validity determination using the content validity index and content validity ratio, and (3) cognitive interviews. Ethical approval was obtained from the institutional ethics committee. Results: Out of the initial 71 items, 18 were removed during content validity assessment, and 7 out of 53 were discarded in the cognitive interview phase. The final scale comprised 46 items, and the universal agreement value was 0.7. Conclusion: The research affirms the measurement tool’s overall good and satisfactory content validity. The removal of items during the validation process indicates methodological rigor. The study’s outcomes contribute not only to the establishment of a reliable measurement tool but also underscore the commitment to rigorous methodologies for valid and meaningful research outcomes.